Efforts to Improve Student Learning Outcomes in Natural Science Lessons Material Plant Body Parts Through Cooperative Type Team Games Tournament in MI Negeri 4 Asahan - Fadhliah (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve the learning outcomes of students in the Natural Sciences subject, especially in the material